Women's Emancipation and Role in Community Development - Rafadi Khan Khayru; Nugrahini Susantinah Wisnujati (metromedia.education, 2022)
Currently the whole world recognizes equal rights and obligations for every citizen, including gender issues. However, the reality shows that women are left behind or disadvantaged more than men, including in the fields of education, health, employment, mastery and utilization of science and technology. Although not all elements of society recognize the role of women in development, several regions have recognized the success of women. Not only in developed countries or big cities but also in small towns. This study aims to determine the role of women in community development. There is a group of women who are aware of the positive potential, and the detrimental factors for them in terms of gender. These adverse factors include trafficking in women, prostitution, marginalization of women, feeling of position as second-class citizens compared to men, and views about women playing less political or bureaucratic roles, and so on.